2018
DOI: 10.1007/s12035-017-0852-4
|View full text |Cite
|
Sign up to set email alerts
|

Brain Photobiomodulation Therapy: a Narrative Review

Abstract: Brain photobiomodulation (PBM) therapy using red to near-infrared (NIR) light is an innovative treatment for a wide range of neurological and psychological conditions. Red/NIR light is able to stimulate complex IV of the mitochondrial respiratory chain (cytochrome c oxidase) and increase ATP synthesis. Moreover, light absorption by ion channels results in release of Ca and leads to activation of transcription factors and gene expression. Brain PBM therapy enhances the metabolic capacity of neurons and stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
286
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(297 citation statements)
references
References 243 publications
4
286
0
7
Order By: Relevance
“…In the past several years, mitochondria have been conclusively demonstrated to be one of the main targets of PBM . One previous study investigated the time response of muscles to PBM, which suggested the importance of finding the optimal time to apply PBM to tissues as a preconditioning regimen .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past several years, mitochondria have been conclusively demonstrated to be one of the main targets of PBM . One previous study investigated the time response of muscles to PBM, which suggested the importance of finding the optimal time to apply PBM to tissues as a preconditioning regimen .…”
Section: Discussionmentioning
confidence: 99%
“…* P < .05 vs control group, # P < .05 vs HI group. Scale bar = 40 μm [37,41,74,75]. One previous study investigated the time response of muscles to PBM, which suggested the importance of finding the optimal time to apply PBM to tissues as a preconditioning regimen [76].…”
Section: Discussionmentioning
confidence: 99%
“…Photobiomodulation employs high influence but low power light from light emitting diode (LED) system or laser sources in wavelength range from 600 to 1000 nm, to modulate mitochondrial respiration in a nonthermal and noninvasive way . Transcranial low‐level laser stimulation of the brain with light at near‐infrared range is a novel form of photobiomodulation, which is well known as low‐level light/laser therapy/treatment (LLLT) on patients . Recently, transcranial low‐level light stimulation attracted wide attentions for its amazing therapeutic potential in various psychological and neurological conditions in the nondestructive manner.…”
Section: Introductionmentioning
confidence: 99%
“…We might consider that the long‐lasting LED effect recorded on the 3rd day of peripheral nerve lesion is due to the recruitment of inhibitory descending neural pathways from the endogenous pain inhibitory system known to be involved in several antinociceptive mechanisms . Recent researches support the ability of light to penetrate the brain tissue and exert biological effects on photoacceptor molecules present in central nervous system structures . Several studies have shown its potential benefits in retinal diseases, stroke, neurodegeneration, neuromuscular disorders, and memory and mood disorders .…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49][50][51] Recent researches support the ability of light to penetrate the brain tissue and exert biological effects on photoacceptor molecules present in central nervous system structures. [52][53][54] Several studies have shown its potential benefits in retinal diseases, stroke, neurodegeneration, neuromuscular disorders, and memory and mood disorders. [55][56][57][58] In addition, the increase of the pain threshold in the right hindpaw of mice (measured by von Frey filaments) was demonstrated after photobiomodulation with infrared (810 nm) applied to different anatomical locations.…”
Section: Discussionmentioning
confidence: 99%